1966
DOI: 10.1029/jz071i019p04495
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric ring currents and the low-latitude disturbance daily variation

Abstract: An asymmetric ring current belt consisting of a symmetric ring current and a superimposed partial ring current system is proposed as the explanation for the low‐latitude disturbance daily variation. The magnetic effects of the partial ring current system are derived using a scale model together with a small magnetometer as an analog computer. The magnetic field of an asymmetric ring current belt is derived by assigning an amplitude A to the partial ring current function and an amplitude S to the (constant) sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
74
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(81 citation statements)
references
References 6 publications
7
74
0
Order By: Relevance
“…[14] Cummings [1966] modeled the asymmetric ring current (symmetric ring current plus partial ring current) and noted that the asymmetric part of the storm field decays much more rapidly than the symmetric part. The asymmetry of the ring current belt would be centered about 1800 LT.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Cummings [1966] modeled the asymmetric ring current (symmetric ring current plus partial ring current) and noted that the asymmetric part of the storm field decays much more rapidly than the symmetric part. The asymmetry of the ring current belt would be centered about 1800 LT.…”
Section: Discussionmentioning
confidence: 99%
“…The time variation of the amplitude of oscillation was diurnal with the maximum a little after the local noon. He suggested that this feature was associated with the asymmetric development of the ring current reported by CUMMINGS (1966), CAHILL (1966) and others.Following the technique of SUGIURA and CHAPMAN (1960), CROOKER and SISCOE (1971) studied the asymmetric part of the low latitude disturbance field. Their data was confined to 12 years of IGY, a period of very high solar activity.…”
mentioning
confidence: 83%
“…The time variation of the amplitude of oscillation was diurnal with the maximum a little after the local noon. He suggested that this feature was associated with the asymmetric development of the ring current reported by CUMMINGS (1966), CAHILL (1966) and others.…”
mentioning
confidence: 83%
“…Akasofu and Chapman, 1964; Cummings, 1966;Frank, 1970;Love and Gannon, 2010). A remarkable dawn-dusk asymmetry is often observed during main phases of magnetic storms, which is attributed to the partial ring current on the dusk side of the Earth (Akasofu and Chapman, 1964).…”
Section: Introductionmentioning
confidence: 99%